Effect of Taraxasterol on the expression of VEGF and CXCR4 in the precancerous lesions of BREAST CANCER in rats - Hongmei Liu; Zhipeng Wang; Changsong Wang; Hui Feng; Zhigang Liu; Ming Guo (Journal of Animal and Plant Sciences, 2025)
The aim of study was to explore the effect of Taraxasterol on VEGF and CXCR4 expression in the precancerous lesions of breast cancer (BC) in rats.One hundred and eighty Sprague-Dawley (SD) rats were randomly divided into control group, model group, low-dose Taraxasterol group, moderate-dose Taraxasterol group and high-dose Taraxasterol group and tamoxifen group. Dimethylbenz[a]anthracene (DMBA) was used to induce the model of dysplasia of BC in rats. After the model was successfully established, different doses of Taraxasterol were used for intervention, and tamoxifen was used as the intervention control. Finally, protein and mRNA levels of VEGF and CXCR4 were detected.The number of rats with atypical hyperplasia in high-dose Taraxasterol group and the tamoxifen group was less than that in model group (P<0.05 or P<0.01). After intervention for atypical hyperplasia rats, VEGF and CXCR4 expression levels in the Taraxasterol groups and Tamoxifen group were better than those in model group (P<0.01). In addition, VEGF and CXCR4 levels in each Taraxasterol groups differed drastically from those in the Tamoxifen group (P<0.01). The mRNA expression intensity of VEGF and CXCR4 of rats in each Taraxasterol group was superior to that of Tamoxifen group (P<0.05 or P<0.01). Taraxasterol can effectively reduce levels of VEGF and CXCR4 in DMBA-induced rat BC precancerous lesions, which may be an effective mechanism for inhibiting angiogenesis and blocking BC.
Keywords: Taraxasterol; breast cancer; Precancerous lesions; Vascular endothelial growth factor; CXCR4